Role of the gut microbiota in human health - Chałupnik, Aleksandra; Chilimoniuk, Zuzanna; Sobstyl, Anna; Dobosz, Maciej; Borkowska, Aleksandra; Wieteska, Małgorzata (Journal of Education, Health and Sport, 2020)
Introduction: The human gut microbiota has become the subject of extensive research in recent years and the knowledge of the species inhabiting the gut is growing rapidly. Microbiota plays an important role in human health and diseases. It takes part in obtaining and storing energy, as well as in metabolic functions. The aim of the study: The purpose of the study is to collect and review scientific publications about the impact of gut microbiota on human health. Material and method: The paper uses standard criteria as the research method. The articles used to create the reviews were published on the PubMed and Google Scholar platforms. Description of the state of knowledge: Numerous studies suggest that composition of intestinal microbiota has impact on the long-term functioning of the human organism. Depressive disorders appear to be associated with changes in the microbiota. In depressed patients, fewer bacteria of the type Bacteroidetes and higher level of Alistipes are found. A few studies have demonstrated a link between gut microbial signatures and hypertension. Studies have shown that T2DM patients may have an altered composition of gut microbiota, mainly a decreased Bacteroidetes/ Firmicutes ratio and decrease in some functional bacteria when compared to healthy people. Intestinal microorganisms are also a key element in the proper functioning of the immune system by influencing the maturation process of the immune system's cells. Summary: To sum up, numerous studies indicate that abnormal composition of the intestinal microflora is the cause of not only faster development of metabolic syndrome, but also other diseases. It influences the development of circulatory, nervous or immune system diseases. Its abnormal composition is influenced by many factors such as diet, lifestyle or antibiotic therapy.